Implementasi Etika Bisnis Islam Dalam Meningkatkan Kinerja Karyawan di Percetakan CV. Citra Medan - Nurul Aflah Harahap; Azhari Akmal Tarigan (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
The research aims to analyze the impact of implementing Islamic Business Ethics on enchancing employee perfomance at CV. Citra Medan Printing. The researcj methodology employed is descriptive qualitative research. Data ware gathered through the researcher’s field observations during an internship at the company and through interviews with the owner of CV. Citra Medan. The result of this studi demonstrate that the implementation of Islamic Business Ethics at CV. Citra Medan Printing has a positive impact on employee perfomance. Employees engaged in business practices aligned with islamic values tend to be more motivated, exhibit higher commitment levels and show improvements is productivity. This study provides recommendations for similar companies to consider implementing Islamic Business Ethics aas a strategy to boost employee perfomance and fortify the company’s image. Furthermore, this research contributes to a deeper understanding of how Islamic Business Ethics can be applied in the context of modern business.